Role of impulsiveness in online purchase completion intentions: an empirical study among Indian customers. Issue 2 (2nd November 2020) - G., Rejikumar; Asokan-Ajitha, Aswathy
Abstract : Purpose: Online cart abandonment is a severe issue posing challenges to e-commerce growth. Emerging economies such as India fascinates global marketing practitioners because of favorable demographics and high levels of internet penetration. This study aims to consider the role of certain exogenous factors in developing shopping motivations that sequentially mediate to online purchase completion through impulsiveness under risk perceptions. The primary motivation behind this study is to understand the mental mechanism among online customers that develop purchase completion intentions, which prevent cart abandonment significantly. Design/methodology/approach: Impact of e-commerce exogenous factors related to e-commerce such as website attributes, product features, promotional excellence and decision-making easiness on shopping motivations, impulsiveness and purchase completions intentions under the moderating effect of risk was estimated from the perceptions of Indian online customers ( n = 243) using variance-based structural equation modeling and SPSS process macro v.3.0. Findings: The most important exogenous variable that can influence purchase completion directly, sequentially through shopping motivations is decision easiness and promotions. Even though utility motivations are dominant in purchase completion intentions, hedonistic aspects are more critical in developing impulsiveness. The translation of impulsiveness to purchase completion is happening, but risk perception significantly moderates impulsiveness formation. Research limitations/implications: Theoretically, this study examined online purchase completions being the most sought response by a customer to various stimuli in e-commerce. The study adopted a moderated mediation analysis in which shopping motivations and impulsiveness were mediators and risk as moderator. The interaction effect of risk on purchase completions was significant even when the mediating effects were prominent. Practical implications: Contributes to the current knowledge-related online buying behavior in virtual retail formats and helps marketers in streamlining their focus in using impulsiveness as a strategic tool in reducing cart abandonment. Originality/value: This study helps in understanding emerging trends in online buying behavior in India.